Estudio experimental sobre el efecto de tres componentes de conocimiento previo en la lectura de textos ingleses por estudiantes de inglés como lengua no nativa - Lahuerta Martínez, Ana Cristina (Miscelánea: A Journal of English and American Studies, 1992)
Research in native (English] and nonnative (English as a second and a foreign language} reading comprehension has shown that the ability to understand texts is based not only on the comprehender's linguistic knowledge, but also on general knowledge of the world and the extent to which that knowledge is activated during processing. Separate components of background knowledge which have been identified in the literature are: (1) prior knowledge in the content area of the text (familiar versus novel); (2) prior knowledge that the text is about a particular content area (context versus no context); and (3) degree to which the lexical items in the text reveal the content area (transparent versus opaque).This paper reports a study which shows the individual and interactive effects of these three separate variables on the reading comprehension of nonnative readers ofEnglish and the quantity and quality (familiarity, context and transparency) of the reproductions which depend on the language used for the reproductions, making half the students write their summaries in their native language (Spanish) and the other half in the nonnative language (English), and comparing the results.Results indicate that two of the three components of background knowledge{transparency and context] play a significant role in reading, understanding and recalling a text, both in English and in Spanish, but show as well that the language (English or Spanish) in which the reproductions are executed conditions the quantity of information reproduced.These findings are discussed in relation to schema theoretical views of reading as an interactive process between the text and the reader, and in relation to their implications for reading pedagogy.